Analysis and detection of homemade explosive TACP - Matyáš, Robert; Jalový, Zdeněk; Vodochodský, Ondřej; Zmrhalová, Zuzana; Maixner, Jaroslav; Lapcak, Ladislav; Baros, Petr; Hausner, Jiri; Kolba, Pavel; Capkova, Zuzana (Elsevier Science, 2024)
This paper focuses on tetraamminecopper(II) perchlorate (TACP), a relatively newly used and popular homemade explosive that is insufficiently described in the literature. The compound was analyzed using commonly used forensic laboratory techniques such as FTIR, Raman, XRPD, and DTA. The TACP molecule was labeled with four N-15 atoms on ammonia ligands to assign vibrational modes to the resulting bands. The paper also describes the thermal decomposition of TACP using thermoanalytical methods TGA/MS. The TACP decomposes to the final product CuO in six distinct ranges, releasing N2O, NO, HCl, O-2, H2O, and NH3. It has been found that TACP is not a stable compound and will decompose spontaneously to ammonia, ammonium perchlorate, and basic copper perchlorate within a few months if exposed to air at room temperature. Residues of precursors have been detected in TACP prepared by four improvised preparation methods published on the Internet. These residues can be used to identify the precursor used in the preparation. The post-blast residues of TACP are of ordinary shape, but the use of TACP as an explosive can be indicated by the presence of a high content of copper and chlorine atoms in post-blast residues. The results of canine detection of TACP indicate that the dog is able to detect TACP, but the dog is likely to focus on the smell of ammonia in the TACP odor.
Analýza a detekce improvizované výbušiny TACP
Keywords: Tetraamminecopper(II) perchlorate; TACP; Forensic analysis; Powder diffraction; FTIR; Raman spectroscopy; chloristan tetraamminměďnatý; TACP; forenzní analýza; rentgenová prášková difrakce, FTIR, Raman